Primus universalis“ u zvaničnim dokumentima Međunarodne komisije za bogoslovski dijalog rimokatoličke i pravoslavne Crkve: recepcija i izazovi - Stevanović, Nebojša (Sabornost, 2023)
The essential idea of the work is reflected in providing an answer to the question of the place and nature of the primus universalis within the framework of the official documents of the International Commission for Тheological Dialogue of the Roman Catholic and Orthodox Churches. On those grounds, in order to determine the planned primatial course, the further course of work continued with the discussion of the challenges and reception of the basic ecclesial positions primus universalis, whereby this part of the work was divided in two directions: the first, manifested in the direction of reception within the framework of the Position of the Moscow Patriarchate according to to the question of the nature of the universal first, and, second, the answer of Metropolitan Elpidophoros Lambriniadis. The diversity and juxtaposition, but also the coexistence, of the two models within the framework of Orthodox ecclesiology is also shown by an example of a rereading of this issue in systematic theology, where the positions of numerous theologians of the same Church are presented, whose analysis confirms the coexistence of a double interpretation of the primus universalis, expressed, in general, in dialectic ’esse — bene esse Ecclesia’.